Institutional and Managerial Ownership, Capital Structure, and Firm Size as Economic Value Drivers: Insights from the IDX Food and Beverage Sector - Aurelia, Gabrella; Melinda, Melinda; Dini, Siti; Sakuntala, Dwita (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the effects of Institutional Ownership, Managerial Ownership, Capital Structure, and Firm Size on Firm Value. The research employs a quantitative method. The population consists of manufacturing companies in the Food and Beverage sub-sector from 2019 to 2023, totaling 95 companies. A sample of 26 companies was selected, yielding 130 data points. Secondary data were used for data collection, and multiple linear regression analysis was applied for data analysis. The results indicate that Institutional Ownership and Managerial Ownership have a positive and significant effect on Firm Value, while Capital Structure and Firm Size do not significantly affect Firm Value. Simultaneously, all variables—Institutional Ownership, Managerial Ownership, Capital Structure, and Firm Size—have a positive and significant effect on Firm Value.